2013
DOI: 10.1007/s00284-013-0391-9
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Scale Analysis of Bacterial Communities Involved in Rocks Colonization and Soil Formation in High Mountain Environments

Abstract: Alpha and beta diversities of the bacterial communities growing on rock surfaces, proto-soils, riparian sediments, lichen thalli, and water springs biofilms in a glacier foreland were studied. We used three molecular based techniques to allow a deeper investigation at different taxonomic resolutions: denaturing gradient gel electrophoresis, length heterogeneity-PCR, and automated ribosomal intergenic spacer analysis. Bacterial communities were mainly composed of Acidobacteria, Proteobacteria, and Cyanobacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The absence of major bacterial taxa in some rhizospheres and bare soil could be explained by the soil chemistry of the acidic ferrous rocks which characterize the valley. In a previous study about five different environmental matrices from Matsch Valley (Esposito et al, 2013), authors found similar patterns. For instance, Proteobacteria were rare in bare soils, representing less than 10% on average, while they were much more abundant in biofilms (40%) or in lichen thalli (50%).…”
Section: Discussionsupporting
confidence: 54%
“…The absence of major bacterial taxa in some rhizospheres and bare soil could be explained by the soil chemistry of the acidic ferrous rocks which characterize the valley. In a previous study about five different environmental matrices from Matsch Valley (Esposito et al, 2013), authors found similar patterns. For instance, Proteobacteria were rare in bare soils, representing less than 10% on average, while they were much more abundant in biofilms (40%) or in lichen thalli (50%).…”
Section: Discussionsupporting
confidence: 54%
“…The nitrogen cycle of the glacial forefield on Anvers Island (Antarctic Peninsula) was dominated by heterotrophic diazotrophs and not by Cyanobacteria (Strauss et al 2012), whereas previous studies on the Arctic environment showed the crucial role of Cyanobacteria species in nitrogen fixation (Zielke et al 2002). The relative importance of Cyanobacteria, however, is still debated, since in many cases they represent only a minor part of the overall bacterial communities in mineral soils, even if the mineral soil is fully exposed to light (Esposito et al 2013). Cyanobacterial communities of the Damma Glacier moraine were quite similar to the ones found in the biological soil crusts of the Chihuahuan Desert, but in Damma they were found to be not shaped in well-organized crusts.…”
Section: Microbial Role In Nutrient Cycling In High Mountain Environmmentioning
confidence: 96%
“…A first insight into the bacterial communities associated with different environmental matrices showed distinct variations among sites: Acidobacteria mostly found in mineral soil; Proteobacteria in sediments, biofilms, and lichens; Cyanobacteria on rock surfaces; and Firmicutes and Bacteroidetes in biofilms (Esposito et al 2013). Among the different environmental matrices of higher Matsch Valley, mineral soil showed the highest bacterial diversity in terms of taxa, even accounting for nitrogen fixing bacteria (Ciccazzo et al 2014b).…”
Section: Microbial Communities In Primary Vegetation Successionsmentioning
confidence: 98%
“…Microbial communities, as free-living cells or in biofilms, are the first colonizers of newly exposed rocks (1). They may influence the rate of mineral weathering and the amount and the quality of organic matter in soil (2). Strain H41 was isolated from a weathered tuff surface using the dilution plating method.…”
Section: Genome Announcementmentioning
confidence: 99%